Near-field and particle size effects in coherent Raman scattering - Ooi, Chong Heng Raymond (‎EMW Publishing, 2011)
Nonlinear optical processes have been used for sensitive detection of chemicals, optical imaging and spectral analysis of small particles. We have developed an exact theoretical framework to study the angular dependence of coherent anti-Stokes Raman scattering (CARS) intensity in the near field and far field for nanoparticle and microparticle. We obtain exact analytical solution for the CARS signal valid for arbitrary detection distance. Interesting angular dependence is found for nanoparticle, especially with near field detection. The study includes the erects of focused lasers and particle size on the CARS intensity distribution. We find that the detection distance and particle size do not affect the spectroscopic peaks of CARS. However, interference of reflected waves in nanoparticle can produce a dip in the backscattered spectrum.